Local Government Finance In The Pandemic: Polish Experience - Marzanna PONIATOWICZ (Communications of International Proceedings, 2021)
Research background: The Covid-19 crisis differs significantly from previous crises, both in terms of its causes, scale, and effects. This, in turn, contributes to the specificity of its impact on the local government finance system, considered in terms of income, expenditure and budgetary outcomes of local government units. Purpose of the article: The aim of the article is not only to determine the specificity of the current pandemic crisis and the way it influenced the finances of local government units in Poland, but also to analyze and evaluate the anti-crisis measures taken in this regard. Research methods: To assess the specificity of the analyzed crisis and its effects, aggregate data of the Ministry of Finance on the implementation of local government budgets were used. Comparisons were made for the three quarters of 2019 and 2020, taking into account changes in: 1) particular categories of budget revenues and expenditure; 2) budgetary outcomes (general and operational); 3) debt of local government units. Findings and added value: The pandemic crisis has become a pretext for the intensification of fiscal centralization processes in Poland. The structure of local government budget revenues deteriorated (the mechanism of masking the decrease in own revenues with the increase in transfer revenues). There has also been an increase in the current budgetary expenditure of local government, and – what is important – a significant part of it is arbitrarily induced by central legal regulations. Another disturbing symptom related to the pandemic crisis is the attempt to centralize the investment activity of local government units (see the Government Fund for Local Investments and the discretionary and untransparent system of granting investment subsidies from it). As a result of the measures described, the fiscal autonomy of local government in Poland weakened. It should be added that the negative effects associated with it accumulate mainly in the largest local government units, i.e., in cities with poviat status.
Keywords: Covid-19 crisis; local government’ budget revenues and expenditure; centralization; local public debt